Faktor-Faktor yang Memengaruhi Kejadian Depresi pada Lansia Berpendidikan Rendah Berdasarkan Indonesian Family Life Survey 5 - Tanuwijaya, Melyana; Suryakusuma, Linda; Turana, Yuda; Handajani, Yvonne Suzy (Majalah Kedokteran Neurosains Perhimpunan Dokter Spesialis Saraf Indonesia, 2023)
Introduction: The prevalence of depression increases with age and a high level of education is a protective factor from depression among elderly. However, majority of elderly in Indonesia are low educated which have an increased risk of depression. Aim: To determine the factors influencing the incidence of depression in low educational attainment elderly. Method: A cross-sectional study using secondary data from the 2014-2015 Indonesian Family Life Survey 5 (IFLS-5) which was conducted on respondents aged 60 years or older with low educational attainment. Depression was assessed using the Center for Epidemiologic Studies Depression Scale-10 (CESD-10), cognitive function was assessed using the Telephone Interview for Cognitive Status (TICS), the intensity of physical activity using the International Physical Activity Questionnaire (IPAQ) short-form, functional disability was assessed using 6 items of Katz Activity Daily Living (ADL) and the Lawton Instrumental Activity of Daily Living (IADL), and other variables using questions in the IFLS questionnaire. Result: Among 3481 respondents in this study, mostly aged 60-74 years (86,4%), women (55,3%), married (63,3%), working (54,9%), doing moderate-high intensity physical activity (64,6%), independent in performing ADL (87,3%), and normal in IADL (73,5%). Addition, most of them did not experience decrease in cognitive function (79,9%), had no history of hypertension (74,1%), diabetes mellitus (95%), arthritis/rheumatism (87,2%), and physical disability (99,2%), also not depressed (83,8%). Based on bivariate analysis, there was a significant relationship between age (p=0,042; RO=0,737), hypertension (p=0,005; RO=1,332), arthritis/rheumatism (p=0,000; RO=1,681), physical disability (p=0,001; RO=3,716), ADL (p=0,000; RO=1,632), and IADL (p=0,000; RO=1,907) with depression in low educational attainment elderly. However, there was no significant relationship between gender (p= 0,091), marital status (p=0,227), occupation (p=0,328), cognitive function (p=0,304), diabetes mellitus (p=0,704), and physical activity (p=0,525) with depression in low educational attainment elderly. In the multivariate analysis it was found that IADL to be the most contributing factor to the incidence of depression among low educated elderly based on IFLS-5 (p=0,000; RO=1,896). Discussion: There was a significant relationship between age, hypertension, arthritis/rheumatism, physical disability, ADL, and IADL with the incidence of depression in low educational attainment elderly with IADL being the most significant factor. Respondents with dependency (IADL) were 1,8 times, respectively, at greater risk of experiencing depression.